Bi-atrial high-density mapping reveals inhibition of wavefront turning and reduction of complex propagation patterns as main antiarrhythmic mechanisms of vernakalant. Issue 7 (26th February 2021) - van Hunnik, Arne; Zeemering, Stef; Podziemski, Piotr; Kuklik, Pawel; Kuiper, Marion; Verheule, Sander; Schotten, Ulrich
Abstract: Aims: Complex propagation patterns are observed in patients and models with stable atrial fibrillation (AF). The degree of this complexity is associated with AF stability. Experimental work suggests reduced wavefront turning as an important mechanism for widening of the excitable gap. The aim of this study was to investigate how sodium channel inhibition by vernakalant affects turning behaviour and propagation patterns during AF. Methods and results: Two groups of 8 goats were instrumented with electrodes on the left atrium, and AF was maintained by burst pacing for 3 or 22 weeks. Measurements were performed at baseline and two dosages of vernakalant. Unipolar electrograms were mapped (249 electrodes/array) on the left and right atrium in an open-chest experiment. Local activation times and conduction vectors, flow lines, the number of fibrillation waves, and local re-entries were determined. At baseline, fibrillation patterns contained numerous individual fibrillation waves conducting in random directions. Vernakalant induced conduction slowing and cycle length prolongation and terminated AF in 13/15 goats. Local re-entries were strongly reduced. Local conduction vectors showed increased preferential directions and less beat-to-beat variability. Breakthroughs and waves were significantly reduced in number. Flow line curvature reduced and waves conducted more homogenously in one direction. Overall, complex propagation patterns were strongly reduced. No substantial differences in drug effects between right and left atria or between goats with different AF durations were observed. Conclusions: Destabilization of AF by vernakalant is associated with a lowering of fibrillation frequency and inhibition of complex propagation patterns, wave turning, local re-entries, and breakthroughs.